Well-posedness of a nonlinear integro-differential problem and its rearranged formulation. (December 2016) - Galiano, Gonzalo; Schiavi, Emanuele; Velasco, Julián
Abstract: We study the existence and uniqueness of solutions of a nonlinear integro-differential problem which we reformulate introducing the notion of the decreasing rearrangement of the solution. A dimensional reduction of the problem is obtained and a detailed analysis of the properties of the solutions of the model is provided. Finally, a fast numerical method is devised and implemented to show the performance of the model when typical image processing tasks such as filtering and segmentation are performed.